2016
DOI: 10.1097/iae.0000000000001288
|View full text |Cite
|
Sign up to set email alerts
|

An Automatic, Intercapillary Area-Based Algorithm for Quantifying Diabetes-Related Capillary Dropout Using Optical Coherence Tomography Angiography

Abstract: Structured Abstract PURPOSE To develop a robust, sensitive, and fully automatic algorithm to quantify diabetes related capillary dropout using optical coherence tomography (OCT) angiography (OCTA). METHODS A 1050 nm wavelength, 400 kHz A-scan rate swept-source OCT prototype was used to perform volumetric OCTA imaging over 3 mm × 3 mm fields in normal controls (n = 5), patients with diabetes without diabetic retinopathy (DR) (n = 7), patients with non-proliferative diabetic retinopathy (NPDR) (n = 9), and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 10 publications
1
85
0
2
Order By: Relevance
“…Recent studies using OCTA as well as FA have quantitatively evaluated capillary nonperfusion areas in DR, and have generally demonstrated that capillary nonperfusion increases with increasing DR severity. 13,20,21 The results herein agree with these findings (Table). Furthermore, compared to FA, OCTA can also visualize periarterial capillary-free zones [16][17][18] and vessel connections at the level of precapillary arterioles and venules.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies using OCTA as well as FA have quantitatively evaluated capillary nonperfusion areas in DR, and have generally demonstrated that capillary nonperfusion increases with increasing DR severity. 13,20,21 The results herein agree with these findings (Table). Furthermore, compared to FA, OCTA can also visualize periarterial capillary-free zones [16][17][18] and vessel connections at the level of precapillary arterioles and venules.…”
Section: Discussionsupporting
confidence: 91%
“…FAZ circularity is proposed to quantify deformation of FAZ indicating disruption of the terminal capillary ring at the fovea 16. Nevertheless, such association between FAZ circularity and VA has not been found by Durbin et al 8.…”
Section: Discussionmentioning
confidence: 99%
“…Automated algorithms quantifying DMI from full retinal thickness angiograms have shown the ability to distinguish DR from healthy controls (Hwang et al, 2016a), as well as trends of avascular area increasing with disease severity (Schottenhamml et al, 2016). Demonstrating the usefulness of OCTA in segmenting the individual capillary plexuses, studies showed that grading DMI in the three distinct plexuses (SCP, MCP, and DCP) had a higher sensitivity and specificity for determining DR versus healthy controls, as well as determining DR stage, compared to grading full retinal thickness angiograms (Zhang et al, 2016b, Hwang et al, 2016b).…”
Section: 5 Ischemia On Oct Angiographymentioning
confidence: 99%